Flavin-based catalysis : principles and applications - Radek Cibulka; Marco W. Fraaije (Weinheim : Wiley-VCH, 2021)
This text gives an overview of a rapidly developing research field, presenting structures and properties of flavin derivatives as well as their proven application as bioinspired catalysts in various organocatalytic, biocatalytic, and photocatalytic reactions.
Structure and Properties of Flavins / Tetiana Pavlovska, Radek Cibulka -- Natural Flavins: Occurrence, Role, and Noncanonical Chemistry / Jeroen Drenth, Marco W Fraaije -- Spectral Properties of Flavins / Marek Sikorski, Igor Khmelinskii, Ewa Sikorska -- Modes of Flavin-Based Catalysis / Radek Cibulka, Marco W Fraaije -- Organocatalytic Monooxygenations / Hiroki Iida, Yasushi Imada -- Flavin-Based Supramolecular and Coupled Catalytic Systems / Hiroki Iida, Yasushi Imada -- Flavoprotein Monooxygenases and Halogenases / Caroline E Paul, Alice Guarneri, Willem JH Berkel -- Flavoprotein-dependent Bioreduction / Helen S Toogood, Nigel S Scrutton -- Flavoprotein Oxidases / Daniel Ouedraogo, Giovanni Gadda -- Benzylic Photooxidation by Flavins / Beiyi Cheng, Burkhard Konig -- New Applications of Flavin Photocatalysis / Eva Svobodo, Radek Cibulka -- Light-Driven Flavin-Based Biocatalysis / Daria Grosheva, Todd K Hyster* -- Index
Keywords: Catalysis; Flavins